OPERATIONAL MANAGEMENT OF THE UMROH PLUSTOUR PROGRAM IN PT. ALAMIN AHSAN TRAVEL - Alwie, Farah Nabilla; Hermawan, Dony (Journal of Indonesian Tourism and Policy Studies, 2021)
This article discusses the operational management of Umrah plus tour packages at PT. Experience Ahsan Travel. The discussion described is the programs owned by Alisan Tours & Travel, preparations by Alisan Tours & Travel in undergoing the operational process of organizing Umrah plus tours, obstacles experienced by Alisan Tours & Travel in organizing Umrah plus tours, and analysis of the implementation of operational management in Umrah plus tour activities at PT Alamin Ahsan Travel. The data collection carried out by the author is based on direct observations in the field and literature studies, in a process carried out from the beginning of the internship to the end. This research is useful as a source of information on the management of plus tour packages.